7/8 is ur answer because
it can be cut into smaller parts
Answer
It is $180
Step-by-step explanation:
You do 450 times 40% and you get $180
(x + 6)(4x + 1)
x times 4x = 4x^2
x times 1 = x
6 times 4x = 24x
6 times 1 = 6
<span>And finally, by adding like terms, 4x^2 + 25x + 6
I hope this helps you! Good luck :)</span>
Here you go you little troll <span>191630195140</span>
Answer:
x = -2
Step-by-step explanation:
5x + 2(x - 4) = 5x + x - 10
First, we need to to multiply out the parathesis in the equation:
5x + 2(x - 4) = 5x + x - 10
5x + 2x - 8 = 5x + x - 10
Next, we can combine "like terms" to simplify the equation further:
5x + 2x - 8 = 5x + x - 10
7x - 8 = 6x - 10
Now we can isolate the variable "x" to one side:
7x - 8 = 6x - 10
x - 8 = -10
x = -2
To check our work, we can replace x with -2 in our original equation:
5x + 2(x - 4) = 5x + x - 10
5(-2) + 2 (-2 - 4) = 5(-2) + -2 - 10
-10 + 2 (-6) = -10 -2 - 10
-22 = -22
I hope this helps!
-TheBusinessMan